Pengaruh Brand Awareness dan Brand Trust terhadap Keputusan Pembelian Fried Chicken pada Allbaik Chicken Cabang Sawah Lebar Kota Bengkulu - Rintan Harumi Prameswari; Karona Cahya Susena; M. Rahman Febliansa (UNIVED Press, 2022)
This study aims to determine the effect of brand awareness and brand trust on the purchasing decision of fried chicken at Allbaik Sawah Lebar Branch, Bengkulu City. The sample in this study were 50 customers who had purchased fried chicken at Allbaik Sawah Lebar Branch, Bengkulu City. Data collection techniques using a questionnaire. The analytical method used is multiple regression analysis, hypothesis testing t and hypothesis testing f. The regression results show that there is a positive influence between brand awareness and brand trust on purchasing decisions at Allbaik Sawah Lebar Branch, Bengkulu City because the regression direction has a positive direction, namely Y = 10.256 + 0.580X1 + 0.396X2. Brand awareness has a significant effect on purchasing decisions at Allbaik Sawah Lebar Branch, Bengkulu City, because the significant value of 0.000 is smaller than 0.05. This means that increasing attention to brand awareness will increase purchasing decisions for Allbaik Sawah Lebar Branch, Bengkulu City. Brand trust has a significant influence on purchasing decisions at Allbaik Sawah Lebar Branch, Bengkulu City because the significant value of 0.007 is smaller than 0.05. This illustrates that the more precise the employee's brand trust, the purchasing decisions will also increase. Brand awareness and brand trust jointly have a significant effect on employee purchasing decisions at Allbaik Sawah Lebar Branch, Bengkulu City, thus the initial hypothesis proposed is proven (Ha accepted). That is, there is a significant influence between brand awareness and brand trust on joint purchasing decisions. The coefficient of determination of R square is 0.562. This means that brand awareness and brand trust affect purchasing decisions by 56.2% while the rest (100-56.2% = 43.3%) is influenced by other causal factors not examined in this study.